Post-Covid-19 recovery and resilience - Hong, Gee Hee,Igan, Deniz,Lee, Do (International Monetary Fund, 2021)
Covid-19 has exacerbated economic and social vulnerabilities across Sub-Saharan Africa (SSA). There is a risk that growth could be lower for longer, with a setback to development. Post-pandemic reforms thus become even more important, especially with constrained scope for fiscal and monetary stimuli. Reforms could boost per capita growth by an additional 0.3-1.3 percentage points, relative to the 1.9 percent average since 2010. Such growth would reduce per capita income doubling time from 37 years to about 22 years. Low-income countries stand to gain the most from reforms. The largest gains come from governance, products markets, and factor accumulation. Importantly, these reforms can be implemented in the post-pandemic environment characterized by weaker social and distributional outcomes
10.5089/9781513570044.001
Keywords: Graue Literatur; COVID-19; Growth; Development; Sub-Saharan Africa; Structural Reforms; Political Economy; Economic Growth and Aggregate Productivity: General; Macroeconomic Analyses of Economic Development; Economywide Country Studies: General; Economywide Country Studies: Africa; Labor; General Financial Markets: General (includes Measurement and Data); Aggregate Factor Income Distribution; Institutions and the Macroeconomy; Demand and Supply of Labor: General; Labor Economics Policies; Labour; income economics; Finance; Commodity markets; Finance: General; Labor markets; Labor market reforms; Commodity exchanges; Income; Macroeconomics; Labor market; Manpower policy